Phosphoric Acid-Activated Carbon From Coffee Grounds and Fly Ash For Efficient Laundry Wastewater Adsorption - Muhari, Emma Hermawati Muhari; Silalahi, Rafael Leonardo; Puspita, Nina; Maryani, Anisya Sri; Sihombing, Rony Pasonang; Adhitasari, Alfiana; Kurnia, Dianty Rosirda Dewi (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Laundry waste that is directly discharged into water bodies causes pollution due to its chemical content, such as phosphate. The adsorption method is chosen as an option to reduce the phosphate content in laundry waste due to its simple preparation and low cost. The adsorbent used is a mixture of coffee grounds and fly ash. The use of coffee grounds is based on the increasing waste from coffee shops, thus being utilized as an adsorbent. The aim of this study is to determine the effectiveness of coffee grounds and fly ash with the best combination of composition and contact time using the adsorption method. The stages begin with the preparation of coffee grounds and fly ash through carbonization and activation using H3PO4. The variations performed consisted of variations in the composition of coffee grounds and fly ash with a total of 1 gram in ratios of 1:4; 2:3; 1:1; 3:2; 4:1 and contact time variations of 15 minutes, 30 minutes, 45 minutes, 60 minutes, and 75 minutes. Based on the research results, the highest percentage of removal was found in the composition variation of coffee grounds and fly ash with a ratio of 1:4 for 75 minutes.